Fluid Flow Analysis of Jacket Cooling System for Marine Diesel Engine 93 Kw - Aguk Zuhdi Muhammad Fathallah; Wolfgang Busse; Fadhil Rizki Clausthaldi (International Journal of Marine Engineering Innovation and Research, 2017)
The main function of cooling system is to control the temperature in the engine. To know the flow in the jacket cooling system for marine diesel engine 93 KW and the couple simulation between 1D modeling and 3D modeling, the methodology used. The analysis process was performed by using 3 diffrent softwares. The methodology to analysis fluid flow is CFD (computational fluid dynamic) with steps were problem identification, literature study, design the jacket cooling system based on the cummin diesel engine 93 KW, 1D modeling of cooling system, 3D modeling fluid flow in jacket cooling system, and conclusion. The input of 3D jacket cooling simulation are mass flow, fluid temperature, wall temperature, and heat transfer. The result from this bachelor thesis is fluid flow in jacket cooling system and another parameter output such as temperature flow and velocity if fluid in the jacket cooling system. The result of the flow in jacket cooling is much turbulance in various are of jacket cooling its mean the jacket cooling have a good enfficiency of heat transfer, and the fluid temperature show the increasing temperature from inlet to outlet because of heat transfer happen in the jacket cooling between wall of jacket cooling and fluid. The engine speed will affect the cooling system, if the engine speed is increasing, the speed of flow will increase because the cylinder block need more coolant and the temperature of cylinder block will increase